The Combination of a Novel GLUT1 Inhibitor and Cisplatin Synergistically Inhibits Breast Cancer Cell Growth By Enhancing the DNA Damaging Effect and Modulating the Akt/mTOR and MAPK Signaling Pathways - Weng, Hao-Cheng; Sung, Chieh-Ju; Hsu, Jui-Ling; Leu, Wohn-Jenn; Guh, Jih-Hwa; Kung, Fan-Lu; Hsu, Lih-Ching (Frontiers in Pharmacology, 2022)
Breast cancer is the most prevalent cancer and the second leading cause of cancer death in women. Cisplatin is a commonly used chemotherapeutic drug for breast cancer treatment. Owing to serious side effects, the combination of cisplatin with other drugs is an effective strategy to simultaneously reduce side effects and increase the anticancer efficacy. GLUT1 is an emerging target for cancer treatment since cancer cells usually consume more glucose, a phenomenon called the Warburg effect. In this study, we found that the combination of cisplatin and a novel GLUT1 inhibitor #43 identified from our previous high-throughput screening exerted a synergistic anticancer effect in MCF-7 and MDA-MB-231 breast cancer cells. Mechanism studies in MCF-7 cells revealed that combination of cisplatin and #43 significantly induced apoptosis, intracellular ROS, and loss of mitochondrial membrane potential. Furthermore, #43 enhanced the DNA damaging effect of cisplatin. Akt/mTOR downstream signaling and the ERK signaling pathway usually involved in cell growth and survival were inhibited by the combination treatment. On the other hand, phosphorylation of p38 and JNK, which may be associated with apoptosis, was induced by the combination treatment. Altogether, our data indicate that oxidative stress, DNA damage, the Akt/mTOR and MAPK signaling pathways, and apoptosis may be involved in the synergism of cisplatin and #43 in breast cancer cells.